Excision of Epulis Granulomatosa with Diode Laser in 8 Years Old Boy - Ghadimi, Sara; Chiniforush, Nasim; Najafi, Mahsa; Amiri, Sepideh (Journal of Lasers in Medical Sciences, 2015)
Results and conclusion: Lasers are useful for soft tissue surgery in modern dentistry, especially in relation to pediatric patients due to the rapid and regular wound healing without sutures. Introduction: Epulis granulomatosa is a lesion which grows from an extraction socket. It can be misdiagnosed with lesions of the same clinical appearance such as: foreign body or pyogenic granuloma, or as a herniation of the maxillary sinus. The most common treatment is surgical excision. Case report: The present article reports an Epulis granulomatosa which was removed with diode laser (810 nm) due to child’s fear related to traditional surgical instruments and bleeding.